2018
DOI: 10.1038/s10038-018-0542-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CACNA1D variants associated with sinoatrial node dysfunction and deafness in additional Pakistani families reveals a clinical significance

Abstract: Sinoatrial node dysfunction and deafness (SANDD) syndrome is rare and characterized by a low heart beat and severe-to-profound deafness. Additional features include fatigue, dizziness, and episodic syncope. The sinoatrial node (SAN) drives heart automaticity and continuously regulates heart rate. The CACNA1D gene encoding the Ca v 1.3 protein expressed in inner hair cells, atria

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…It is also in line with previous studies in mice (for a review, see [3]) and humans [24,25]. These found that heterozygous loss-offunction of Cav1.3 is unlikely to cause symptomatic neurodevelopmental disorders and even homozygous loss of Cav1.3 function has not been reported to cause neuropsychiatric behavioral changes [3,24,25,41]. Therefore, a unifying feature of all pathogenic mutations described so far is the potential to induce gating changes that can enhance Cav1.3 function during neuronal activity.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It is also in line with previous studies in mice (for a review, see [3]) and humans [24,25]. These found that heterozygous loss-offunction of Cav1.3 is unlikely to cause symptomatic neurodevelopmental disorders and even homozygous loss of Cav1.3 function has not been reported to cause neuropsychiatric behavioral changes [3,24,25,41]. Therefore, a unifying feature of all pathogenic mutations described so far is the potential to induce gating changes that can enhance Cav1.3 function during neuronal activity.…”
Section: Discussionsupporting
confidence: 91%
“…This nicely fits our prediction that only CACNA1D mutations which can also support channel gain-of-function confer high risk for neurodevelopmental disorders. It is also in line with previous studies in mice (for a review, see [3]) and humans [24,25]. These found that heterozygous loss-offunction of Cav1.3 is unlikely to cause symptomatic neurodevelopmental disorders and even homozygous loss of Cav1.3 function has not been reported to cause neuropsychiatric behavioral changes [3,24,25,41].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As a corollary, our study indicates that functional association of L-type Ca v 1.2 channels and f-channels is not sufficient to maintain normal SAN pacemaking and heart automaticity. Finally, our study provides new mechanistic insight into congenital and autoimmune SAN dysfunction and atrioventricular block based on SAN-VGCC loss-of-function 29,30,49 . Animals were housed in individual cages with free access to food and water and were exposed to 12-h light/dark reverse cycles (light, 20:00 h to 8:00 h) in a thermostatically controlled room.…”
Section: Resultsmentioning
confidence: 87%